PENGARUH PROMOSI, IMAGE JURUSAN, HARGA, DAN LOKASI TERHADAP KEPUASAN SISWA - ., Suyamto (KELOLA, 2013)
The purpose of this research was to prove the influence of promotion, Image of program study, price and location to studentsâ satisfaction at The State Vocational High School 4 Klaten individually and simultaneously. The Hypothesis in this research were : there was significant influence among promotion, Image of program study, price and location to studentsâ satisfaction at The State of Vocational High School 4 Klaten individually and simultaneously as well. The method used in this research was a survey using questionaries for getting data. Population was students at The State of Vocational High School 4 Klaten. Sample taken with a quota random sampling. The test had done with a multiple regression, t test, F test and R 2 . Regression model test showed that promotion, Image of program study price and location had significance influence toward studentsâ satisfaction individually. The Result F test showed that promotion, Image of program study, price and location had significance influence toward students satisfaction simultaneously and R test had 0,940 so the independent variables could explain dependent variables was more 94,0%. The result of test which had been conducted with the regression model , t test, F test and also R test had proved that The fourth of the variables above could become the predictor to the variable of studentsâ satisfaction. Keyword : promotion, Image of program study, price, location, satisfaction.